Oral manifestations due to radiotherapy in geriatric patients with head and neck cancer - Gilda Lucia Garcia-Heredia; Maritza Osorio Nuñez; Ivonne Chong Rivas; Jorge Juan Marinello Guerrero; Diana Garcia del Barco (Editorial Ciencias Médicas, 2018)
Introduction: severe adverse effects are the main cause for interrupting radiotherapy sessions, a fact that has a negative repercussion in the therapeutically benefit expected from theses interventions. Therefore, the dental surgeon's involvement in designing and practicing these dental management protocols in patients with cancer is so important as the oncospecific therapies scheme. The control of unfavorable oral conditions before treatment is a protection factor and conditions therapeutic continuation and success. Objectives: to identify adverse events as a result of radioionic treatment and determine the relationship between adverse events and pre-existing oral conditions in geriatric patients with head and neck cancer. Methods: adescriptive, prospective and longitudinal study was carried out in 72 geriatric patients with head and neck cancer and who were receiving radiotherapy. The oral health status was evaluated right before and during treatment, based on the guidelines of common toxicity criteria. The variables studied were age, gender, topographic site, clinical stage, oral health status, severity of adverse effects and interruptions of radiotherapy. Data processing was performed using the programs SPSS 11.0 and Epidat. Results: 67 % of the patients were included in the age group of 60-69 years, 70 % were men. 67 % of all examined patients had an oral condition that was unfavorable and, out of these, 56 % had to interrupt the radiotherapeutic treatment. From the radiotherapy session number 20 on, corresponding to 40 Gy, all the patients presented at least one adverse effect. The main adverse events were dysgeusia, xerostomia and radiomucositis. A significant association was proved between the adverse effects of radiotherapy and the unfavorable oral conditions prior to the start of treatment. Conclusions: the results indicate that oral assessment in dentistry before, during and after oncoespecific therapy should be a common practice in the care of patients with head and neck cancer, since the interruption of radiotherapy due to the worsening of adverse effects negatively influence the effectiveness of this therapy.